Leveraging social media for business development: an empirical analysis of fan loyalty and fan expansion - Reza Mohammadkazemi; Mohammad Falahat (Cogent Business & Management, 2024)
This study investigates the role of social media in driving business development for Danish professional football clubs. It particularly examines how social media engagement impacts fan loyalty, fan size, and overall business growth. We employed structural equation modeling (SEM) to analyze data from a total sample of 127 participants, collected through questionnaires distributed to club directors and fans across Denmark. The findings reveal that social media fan pages significantly contribute to business growth, with leading social media platforms playing a crucial role. Specifically, social media engagement enhances both fan loyalty and fan size, which directly impacts the overall business development of football clubs. Theoretically, this research introduces a new model elucidating how premier social media platforms influence fan loyalty, fan size, and the overarching business development of football clubs. It expands our understanding of brand loyalty and business growth within the social media context. Practically, it provides actionable insights for club stakeholders on effectively utilizing social media platforms to foster fan loyalty, grow their fan base, and achieve substantial business growth. This study makes a novel contribution to the academic literature on sports club business development through social media. It offers both theoretical and practical insights into effective commercial strategies that clubs can employ to leverage social media engagement, marking a significant step forward in football club commercial strategy.
Keywords: 650; Social media; business development; fan expansion; fan loyalty; football club